Supporting First Nations and Métis Post-Secondary Students’ Academic Persistence: Insights from a Canadian First Nations-affiliated Institution - Kristoff, Tania; Cottrell, Michael (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur, 2021)
Post-secondary institutions have a critical role to play in addressing the Truth and Reconciliation Commission (TRC) Calls to Action through indigenization strategies (TRC, 2015) but, to date, it has proven challenging. In this study, the research lens was expanded to focus on First Nations-affiliated post-secondary institutions, since these come closest to providing authentic approaches to indigenization. The purpose of this qualitative case study was to explore how social support affects the academic persistence of First Nations and Métis students at a First Nations-affiliated post-secondary institution. The findings revealed that administrative and pedagogical practices, consistent with Indigenous ontologies, enabled students to respond to challenges stemming from the generational effects of colonization, and promoted individual and familial advancement, cultural growth and identity formation, community development, and Indigenous sovereignty. It is concluded that mainstream institutions can benefit from the findings as First Nations-affiliated post-secondary institutions provide valuable understandings of potential transformations toward indigenization.